Cyberbullying, educational right and civil responsibility: a legal and deontological analysis of the brazilian reality - Rezende, Elcio Nacur; Calhau, Lélio Braga (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
This article aims to investigate Cyberbullying and the civil responsibility of schools in Brazil. It sought to analyze aspects of students' digital life, accelerated social relations in the "performance society", the competitiveness between private schools, and how it provides a negative environment that facilitates the emergence of Cyberbullying. It was concluded that, with the advent of the first three federal laws dealing with bullying and cyberbullying in Brazil (2015-2018), the malicious omission of schools to comply with the norms described in these laws entails an effective harm to the whole school community. unprotected for not having an effective and permanent program of prevention and control of acts of Cyberbullying. We used bibliographical research and doctrinal notes to carry out this work.